Edukasi Cakap Finansial Sejak Dini Guna Mengantisipasi Tantangan Generasi Sandwich Pada Zaman Modern - Bleskadit, Hendrik B.; Bleskadit, Novalia Herlina (UNIVERSITAS CENDERAWASIH, 2023)
This service activity aims to provide financial literacy educational training from an early age to anticipate the challenges of the sandwich generation in the modern era. The activity is carried out with the aim of carrying out community service activities that are able to explain the sandwich generation phenomenon and its impacts, help the public understand financial management and planning by studying knowledge and applying it by saving and investing, and become an alternative in overcoming problems in the sandwich generation. Service activities are carried out for the young generation of STT Baptist Papua for 1 day, with predetermined criteria or considerations. The material discussed is Personal Financial Management and Planning to make it better. Keywords: Training, Education, Management, Finance, Sandwich Generation